The Influence of Brand Equity, Product Quality, and Customer Satisfaction on Repurchase Intention of Scarlett Skincare in Batam City - Simarmata, Rona Natalia; Husein, Alice Erni (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
Due to air pollution and also the trend of the global skincare industry which has been experiencing rapid growth in recent years, this has increased the demand for skincare products that focus on skin protection in Batam City. The evaluation of a customer's intention to repurchase a product can be determined by two key factors. One of the crucial factors for customers when deciding to repurchase is the quality of the product. Despite this, some users have reported issues with Scarlett products, such as skin irritation, breakouts, and ineffective results like brightening or moisturising. The main goal of the researcher is to examine how independent variables like brand equity, product quality, and customer satisfaction impact the likelihood of a customer repurchasing a product. The research approach utilised in this study is quantitative. There are two types of variables involved in this investigation - independent variables (brand equity, product quality, and customer satisfaction) and a dependent variable known as repurchase interest. The findings from this study indicate that brand equity, product quality, and customer satisfaction play a significant role in influencing the interest in repurchasing Scarlett skincare products in Batam City. Brand equity and product quality contribute to customer loyalty, while customer satisfaction promotes repeat purchases.